Beiträge zur Insektenfauna der DDR: Lepidoptera - Pyralidae (s. str.). - Rinnhofer, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1975)
Seven species of the family Pyralidae occur on the territory of the GDR, and some of them may become economically significant by attacking stores. While six species are widely distributed and sometimes rather frequent, one species, Aglossa caprealis, is known only from four finds in the district of Rostock. When the absence of more frequent species was reported from some districts, this was indubitably due to insufficient searching in these areas. The districts in which the fauna has not been thoroughly investigated in this respect are primarily Schwerin and Suhl, but also Cottbus and Karl-Marx-Stadt. On the basis of the evaluation of publications and the revision of collections, the distribution of the species in the GDR and their mode of life are described. The key is supplemented by eight photos of the right wing pairs of all species and by drawings of the male and female genitals.